2016
DOI: 10.1017/s0950268816000030
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the epidemiology of Escherichia coli ST131 and the impact of interventions on the community and healthcare centres

Abstract: ST131 Escherichia coli is an emergent clonal group that has achieved successful worldwide spread through a combination of virulence and antimicrobial resistance. Our aim was to develop a mathematical model, based on current knowledge of the epidemiology of ESBL-producing and non-ESBL-producing ST131 E. coli, to provide a framework enabling a better understanding of its spread within the community, in hospitals and long-term care facilities, and the potential impact of specific interventions on the rates of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Twelve studies simulate treatment with antibiotics from multiple classes [35, 53, 55, 56, 67, 73, 82, 88, 90, 93, 96, 103]. Treatment with beta-lactams (including carbapenems, cephalosporins and penicillins) is most frequently simulated ( n = 17), while fluoroquinolone [53, 67, 73] and macrolide [82, 90, 93, 103] treatments are simulated less often. The single example of treatment with tetracycline concerns the spread of tetracycline-resistant Escherichia coli in pigs [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies simulate treatment with antibiotics from multiple classes [35, 53, 55, 56, 67, 73, 82, 88, 90, 93, 96, 103]. Treatment with beta-lactams (including carbapenems, cephalosporins and penicillins) is most frequently simulated ( n = 17), while fluoroquinolone [53, 67, 73] and macrolide [82, 90, 93, 103] treatments are simulated less often. The single example of treatment with tetracycline concerns the spread of tetracycline-resistant Escherichia coli in pigs [34].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, individual or ABM represent the system as a population of heterogeneous entities engaged in local interactions; models of this type better capture the stochastic behaviour of a system but impose opportunity costs related to model construction, parameterisation and computing time [114]. Opatowski and colleagues [30] argue that increasingly realistic predictions arising from ABM models are likely to advance the utility of computer simulations for 1 month ⩽ x <1 year [42] 1 year ⩽ x <10 years [35,37,41,42,64,67,70,71,73,88,90,97] 10 years ⩽ x <50 years [59,66,89,92,93,99,101,103] 50 years ⩽ x [ 59,66,79,93,94,102] Undefined time steps [109] Undefined steady state [46,51,53,63,110] Distribution of values reported as mean or range 1 week ⩽ x <1 month [55] 1 month ⩽ x <1 year [82] 1 year ⩽ x <10 years [49,56,69,72,83] 10 years ⩽ x <50 years [36,…”
Section: Model Type and Contextmentioning
confidence: 99%
“…In hospitals, the risk factors found (dependence for basic activities and urinary catheter) might also be associated with increased need for care and contact. These results suggest that direct contact would be a prominent mechanism of transmission for ST131 and build on the concept that avoiding such direct person-to-person transmission would be critical to reduce the spread of these isolates [ 9 ].…”
Section: Discussionmentioning
confidence: 98%
“…Studies focused on ESBL producers (including isolates belonging to ST131) in nursing homes suggested that behaviour was more like households than hospitals [25]. A mathematical model showed that avoiding person-to-person transmission was more efficacious than reducing exposure to antibiotics [26]. a This patient was colonized with non-ST131 CTX-M-1-producing Escherichia coli belonging to D2 group.…”
Section: Discussionmentioning
confidence: 99%